The validity of 23 clinical tests in determining shoulder instability - Tzannes, A.; Walton, J.; Murrell, G. (2000)
The diagnosis of shoulder instability may be determined by the patient's history. The examination has been used to determine the direction and extent of the instability. Whether or not the shoulder examination can be used to diagnose shoulder instability is yet to be determined